An Oceanic Cold Reversal during the last deglaciation - STENNI, BARBARA; Masson Delmotte V.; Johnsen S.; Jouzel J.; Longinelli A.; Monnin E.; Röthlisberger R.; Selmo E. (2001)
A detailed deuterium excess proÞle measured along the Dome C EPICA (European Project for Ice Coring in Antarctica) core reveals the timing and strength of the sea surface temperature changes at the source regions for Dome C precipitation. We infer that an Oceanic Cold Reversal took place in the southern Indian Ocean, 800 years after the Antarctic Cold Reversal. The temperature gradient between the oceanic moisture source and Antarctica is similar to the Dome C sodium proÞle during the deglaciation, illustrating the strong link between this gradient and the strength of the atmospheric circulation.